(3QjMGfI GdQhM aj QSe GdSGYGJ Ydi eSJhi GdSWhMs - (3GHf eYQha , eMeO Hf eYQha GdCSOj GdQUGO, Jbj GdOjf,J (B993 (3g` s
(3ChdgG (B:s
(3jGef CHQR , ef Cab GdEHOGY , TehS GdYbhd hHYO , adeG cGfJ eYQaI ChbGJ GdYHGOGJ ef aQhV GdcaGjI CMHHJ Cf CMQQ ajgG gPg GdQSGdI HWQGFb bWYjI GdHQGgjf s
(3BNQgG (B:s
(3JfHjg(B: (3eG EfbdHJ LgI GdbWH ajg EfbdH ajg hVY GdeMhQ , adG JZad Yf eYQaI GdLgGJ GdSWMjI bHd GdTQhY ai GdQSe CHOkG , aEfg ege ai CeQ GdQSe CjVkG hbO GfJgi eG bUOJ Edi JMQjQg s
(3HgG LOGhd hCTcGds
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjagG HbQjI GdafObs
(3ef bQi fGHdS YGe (B975 (3g` hQJHgG Ydi ebOeI hKdGKI CHhGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3Gdadcs